phi meson electroproduction at low transferred momentum - Afraa Kanaan; Khalid Hamad; Ali Alzubadi (مجلة جامعة الانبار للعلوم الصرفة, 2022)
The electroproduction of phi meson is analyzed. The  amplitude consist of two terms, the soft and the hard pomeron terms. it is assumed, that both pomerons are Regge poles. In the present approach, the two pomeron amplitude for the photoproduction processes is extended to construct an amplitude for the electroproduction processes by introducing the photon virtual mass ( . The  residues of the two poles become functions of ( . These functions are extracted by fitting the differential cross section (  )  of the extended  model at constant energy  to the experimental data using the chi- square method. At each , the hard and the soft terms are multiplied by the factors  and  to match the data. The vertices of the pomeron coupling to the interacting particles are calculated by the dimensions of the vertices which are related to the masses of the interacting particles at each vertex.